2015
DOI: 10.1002/pca.2570
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of tannins and related polyphenols in commercial products of tormentil (Potentilla tormentilla)

Abstract: Underground parts of tormentil are a source of oligomeric proanthocyanidins and ellagitannins, but in smaller quantity of gallotannins. Monogalloylquinic acids are new identified compounds, which had not been described in Potentilla tormentilla before we started our research. In the analysed tormentil tinctures agrimoniin concentration is lower in relation to other tannins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Among the flavan-3-ols, we identified six compounds: (+)-catechin ( 6 ) and five oligomeric procyanidins type B—two PC dimers ( 2 , 11 ), two PC trimers ( 5 , 20 ), and a PC tetramer ( 22 ), which had characteristic pseudomolecular (compound 6 ), or fragment (compounds 2 , 5 , 11 , 20 , 22 ) ions at m / z 289.0723 and others [ 32 ]. Oszmiański et al [ 3 ], in addition to these compounds, also identified (–)-epicatechin.…”
Section: Resultsmentioning
confidence: 99%
“…Among the flavan-3-ols, we identified six compounds: (+)-catechin ( 6 ) and five oligomeric procyanidins type B—two PC dimers ( 2 , 11 ), two PC trimers ( 5 , 20 ), and a PC tetramer ( 22 ), which had characteristic pseudomolecular (compound 6 ), or fragment (compounds 2 , 5 , 11 , 20 , 22 ) ions at m / z 289.0723 and others [ 32 ]. Oszmiański et al [ 3 ], in addition to these compounds, also identified (–)-epicatechin.…”
Section: Resultsmentioning
confidence: 99%
“…The minor phytoconstituents of the analyzed extract were glycoside derivatives of ellagic acid. Fecka et al (2015) reported that the main components of the tormentil tinctures were oligomeric tannins with an average content of 5.26 mg/g, procyanidin C2 (3.36 mg/g) and agrimoniin (2.05 mg/g). Table 1 contains detailed UV-VIS and MS data for all the detected compounds together with their preliminary or full identification.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction procedures applied for agrimoniin determination in plants and commercial products (Table ) are generally solid–liquid extraction (SLE) using acetone, 70% acetone solution, 60% acetone solution, 50% aqueous methanol solution, pure methanol, pure water, or hot water . It has been reported that ellagitannins may be unstable if treated with higher temperatures, resulting in their decomposition to ellagic acid .…”
Section: Analytical Approaches For Agrimoniin Determinationmentioning
confidence: 99%